Automotive Mechatronics: Operational and Practical Issues Volume I - Fijalkowski, B. T. (Springer, 2012)
This book presents operational and practical issues of automotive mechatronics with special emphasis on the heterogeneous automotive vehicle systems approach, and is intended as a graduate text as well as a reference for scientists and engineers involved in the design of automotive mechatronic control systems.